2020
DOI: 10.5194/bg-2020-135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling dynamic interactions between soil structure and the storage and turnover of soil organic matter

Abstract: Abstract. Models of soil organic carbon (SOC) storage and turnover can be useful tools to analyze the effects of soil and crop management practices and climate change on soil organic carbon stocks. The aggregated structure of soil is known to protect SOC from decomposition, and thus influence the potential for long-term sequestration. In turn, the turnover and storage of SOC affects soil aggregation, physical and hydraulic properties and the productive capacity of soil. These interactions have not yet … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…(2021), Meurer, Chenu, et al. (2020) obtained a good model data match. Such promising approaches require the initial soil components as 3D spatially distributed specific data.…”
Section: Mechanistic Modelingmentioning
confidence: 88%
“…(2021), Meurer, Chenu, et al. (2020) obtained a good model data match. Such promising approaches require the initial soil components as 3D spatially distributed specific data.…”
Section: Mechanistic Modelingmentioning
confidence: 88%
“…Several meta-analyses show that soil organic carbon concentrations are larger under RT and NT systems in the uppermost soil layers Bai et al, 2019), especially in fine-textured soils. The reasons for this are the lack of soil disturbance that promotes a stable aggregated structure, which affords a greater physical protection of C against microbial mineralization (Kan et al, 2021) and the elimination of physical mixing and redistribution of C within the topsoil due to the absence of soil inversion by plowing (Meurer et al, 2020b). Meta-analyses have shown that the accumulation of SOM typically found in surface soil layers under RT and NT systems, which reflects the deposition and accumulation of plant residues, is paralleled by a greater microbial biomass (Li et al, 2020c;Spurgeon et al, 2013;Zuber and Villamil, 2016;Chen et al, 2020;Li et al, 2020d) and increases in enzyme activities Zuber and Villamil, 2016).…”
Section: Tillage Systemsmentioning
confidence: 99%
“…They contribute directly and indirectly to the growth and development of plants (HICKS et al, 2020;KÁTAI, 1999KÁTAI, , 2006KÁTAI et al, 2014KÁTAI et al, , 2020SZILI-KOVÁCS et al, 2009, 2011ZHAO et al, 2013), where the degraded organic matter acts as a nutrient source for the soil heterotrophic organisms. Another positive effect of soil organic matter supply and its transformation is the part of the organic matter which is converted to humus, which can, consequently, improve the soil-water-air relationship (MEURER et al, 2020).…”
Section: Introductionmentioning
confidence: 99%